Peran Event Marketing, Sosial Media Marketing, dan Content Marketing Terhadap Minat Beli - Adinata, Patrick Vivid; Cahyaningrum, Brigita N; Margaretha, Betchy Y; Putra, Nicko Kornelius (Universitas Katolik Darma Cendika, 2025)
ABSTRACT The apparel industry in Yogyakarta has experienced rapid growth, leading to intensified competition in the market. This study investigates the influence of event marketing, social media marketing, and content marketing on consumer purchase intention for CRSL Store, both collectively and individually. CRSL Store, a leading local brand in Yogyakarta, uses various development strategies to maintain consumer interest, including organizing music events (CRSL Concert), leveraging social media platforms (Instagram and Tik-Tok), and implementing content-based marketing initiatives. This study adopted a survey-based approach, using questionnaires as the main data collection tool, total of 112 valid respondent, who were selected based on certain criteria: familiarity with the CRSL brand, attendance at CRSL Concert #4, and age range of 17-35 years. Data analysis involved validity and reliability assessment, classical assumption test, multiple linear regression analysis, and hypothesis testing. The findings showed that social media marketing and content marketing had a significant positive impact on consumers' purchase intention for CRSL Store. In contrast, event marketing showed no significant effect. These results indicate the importance for CRSL Store to priorities and improve its social media marketing and content marketing strategies to better capture and retain consumer interest. Keywords: event marketing, social media marketing, content marketing, purchase intention, marketing strategy. ABSTRAK Industri pakaian jadi di Yogyakarta telah mengalami pertumbuhan yang pesat, yang mengarah pada persaingan yang semakin ketat di pasar. Penelitian ini menyelidiki pengaruh event marketing, social media marketing, dan content marketing terhadap minat beli konsumen untuk CRSL Store, baik secara kolektif maupun individual. CRSL Store, sebuah merek lokal terkemuka di Yogyakarta, menggunakan berbagai strategi pengembangan untuk mempertahankan minat konsumen, termasuk menyelenggarakan acara musik (CRSL Concert), memanfaatkan platform media sosial (Instagram dan TikTok), dan menerapkan inisiatif pemasaran berbasis konten. Penelitian ini mengadopsi pendekatan berbasis survei, menggunakan kuesioner sebagai alat pengumpulan data utama sebanyak 112 responden, yang dipilih berdasarkan kriteria tertentu: keakraban dengan merek CRSL, kehadiran di Konser CRSL #4, dan rentang usia 17-35 tahun. Analisis data melibatkan penilaian validitas dan reliabilitas, uji asumsi klasik, analisis regresi linier berganda, dan pengujian hipotesis. Temuan ini menunjukkan bahwa social media marketing dan content marketing memberikan dampak positif yang signifikan terhadap minat beli konsumen CRSL Store. Sebaliknya, event marketing tidak menunjukkan pengaruh yang signifikan. Hasil ini menunjukkan pentingnya bagi CRSL Store untuk memprioritaskan dan meningkatkan strategi social media marketing dan content marketing untuk menangkap dan mempertahankan minat konsumen dengan lebih baik. Kata kunci: event marketing, social media marketing, content marketing, purchase intention, strategi pemasaran.